The Effectiveness of Utilizing Radio Frequency Identification (RFID) in Efforts to Improve the Performance of Security Officers at the Class I Pondok Bambu State Detention Center - Dian Wahyudin; Hasnizam Shaari (Jurnal Mamangan, 2025)
Overcrowding in correctional facilities, particularly at the Class I Pondok Bambu Detention Center, has created significant challenges for maintaining the effectiveness of security patrols. This study aims to evaluate the effectiveness of Radio Frequency Identification (RFID) technology in enhancing the accountability and performance of patrol officers. The research is grounded in organizational effectiveness theory, specifically the goal attainment, system resource, and internal process approaches. Employing a qualitative descriptive case study design, the study involved key informants including the head of the security unit, shift commanders, and security officers. Data were collected through in-depth interviews, observation, and document analysis, and analyzed thematically using the Miles and Huberman framework with triangulation to ensure credibility. The findings demonstrate that the implementation of RFID improved officers’ compliance with patrol checkpoints, strengthened transparency in patrol reporting, and enhanced response time to security incidents. The study concludes that RFID serves as an effective technological tool to support accountability, discipline, and organizational effectiveness within correctional institutions. The novelty of this research lies in its contextual contribution as one of the first empirical studies in Indonesia to investigate the application of RFID in correctional facility security management, expanding its utilization beyond industrial and commercial settings.